Achieving breakthrough performance caused by optimized metal foam flow field in fuel cells. (13th August 2019) - Park, Ji Eun; Hwang, Wonchan; Lim, Myung Su; Kim, Sungjun; Ahn, Chi-Yeong; Kim, Ok-Hee; Shim, Jae-Goo; Lee, Dong Woog; Lee, Ji Hyun; Cho, Yong-Hun; Sung, Yung-Eun
Abstract: Enhanced mass transport in polymer electrolyte membrane fuel cells (PEMFCs) is required for achieving high performance because concentration losses dominate cell performance. In particular, the flow field is crucial for mass transport. Recently, metal foam has been proposed as an alternative flow field owing to its three-dimensional pores, high porosity, and enhanced electrical conductivity. Here, we inspect the microstructure of various copper foams and investigate its effect as a flow field on PEMFCs. The PEMFCs with the optimized foam flow field deliver the highest performance reported to date. A large contact area and small ribs of the optimized foam flow field are advantageous for mass transfer and ohmic resistance. In addition, the internally generated pressure increases the partial pressure of the reactant, which leads to increased performance. This foam flow field has a significant potential for achieving high cell performance by enhancing the electrochemical reaction of the catalyst. Graphical abstract: Image 1 Highlights: Foam structures in foam flow field membrane-electrode assembly (MEA) is investigated. Foam flow field MEA exhibits the 2-fold enhancement compared to conventional MEA. The performance enhancement is due to the internally generated pressure inside foam. Carbon monoxide test shows that more reactants are diffused into the catalyst layer.